Sosialisasi Perangkat Pembelajaran Matematika Kelas II Dengan Pendekatan CRT Materi Pecahan - Yuwenisa Aulia; Zalza Luthfiatun Nisa; Lutfi Ardiansyah; Putri Zudhah Ferryka (CV. ITTC INDONESIA, 2024)
The teaching of mathematics, especially the topic of fractions, requires an interactive and practical approach to help students better understand the concepts. This study aims to develop a training program for mathematics learning on the topic of 'Fractions' using the Discovery Learning model combined with the CRT (Culturally Responsive Teaching) approach for third-semester PGSD students at Universitas Widya Dharma Klaten. The training allows students to explore and discover the concept of fractions through group activities involving visual learning media, namely the Fraction Cake Board. The research method applied is a qualitative approach with observation and interviews to assess the effectiveness of the training. The results show that the training successfully enhanced the students' understanding of fractions and strengthened their ability to apply the concept in real-life situations. Overall, the implementation of Discovery Learning and the CRT approach in mathematics education proved to be effective in increasing student engagement and learning outcomes.